Investigating the impact of the Science Writing Heuristic on student learning in high school chemistry - Arnold, Patricia A. (My University, 2011)
George D. Nelson, former director of the American Association for the Advancement of Sciences Project 2061 said, "Without a science-literate population, the outlook for a better world is not promising." Ten years into the 21st century, the nation's approach to science education continues to struggle in the development of scientific literacy. This study builds on past research that links the use of inquiry in the science classroom toward improvement of science literacy and overall conceptual understanding of scientific principles. Specifically, this study examined the effects of the use of the Science Writing Heuristic (SWH) on student learning in a high school chemistry classroom. Participants in this study were divided into two groups: a control group that used a traditional, directed inquiry approach generated from their textbook, and a treatment group that involved a guided inquiry approach based on the SWH. Two assessments were administered in a pre/post fashion to determine if the use of the SWH in a high school chemistry laboratory improved conceptual understanding of the gas laws and overall student scientific reasoning. Results showed that there were no significant learning gains in the treatment group (SWH) as compared to the control group with regards to either conceptual understanding of the gas laws or in student scientific reasoning ability. This lack of significance may be attributed to the short duration of the study, which in turn resulted in only one learning unit used for comparison in this study. This limitation supports the belief that improvement of scientific literacy and scientific reasoning through the use of the SWH does not occur over the short term. In order to demonstrate measurable improvement in conceptual understanding and scientific reasoning, the SWH needs to be implemented in a holistic fashion that covers several instructional units.
This file was last viewed in Adobe Reader 10.1.1
Keywords: Science--Study and teaching (Secondary); Inquiry-based learning.; Heuristic--Study and teaching (Secondary)